Deploying artificial intelligence in services to AID vulnerable consumers - Erik Hermann; Gizem Yalcin Williams; Stefano Puntoni (Journal of the Academy of Marketing Science, 2023)
Despite offering substantial opportunities to tailor services to consumers' wants and needs, artificial intelligence (AI) technologies often come with ethical and operational challenges. One salient instance of such challenges emerges when vulnerable consumers, consumers who temporarily or permanently lack resource access or control, are unknowingly discriminated against, or excluded from the marketplace. By integrating the literature on consumer vulnerability, AI for social good, and the calls for rethinking marketing for a better world, the current work builds a framework on how to leverage AI technologies to detect, better serve, and empower vulnerable consumers. Specifically, our AID framework advocates for designing AI technologies that make services more accessible , optimize customer experiences and journeys interactively , and to dynamically improve consumer decision-making. Adopting a multi-stakeholder perspective, we also discuss the respective implications for researchers, managers, consumers, and public policy makers.
Keywords: 330; Artificial intelligence; Service; Vulnerable consumers; Ethics; Justice